2019
DOI: 10.1590/18069657rbcs20180085
|View full text |Cite
|
Sign up to set email alerts
|

Potassium Fertilization of Eucalyptus in an Entisol in Low-Elevation Cerrado

Abstract: Potassium (K) is one of the most highly accumulating nutrients in Eucalyptus and, consequently, is heavily exported by the harvesting of wood. Moreover, its availability in the soil in most Brazilian plantation areas is very low, especially in the regions of the Cerrado biome, which has soils with low natural fertility and marked water deficits, implying a lack of nutrient supply and, consequently, a less efficient water use. Our objective was to evaluate the effects of K fertilization on Eucalyptus biomass yi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 23 publications
(41 reference statements)
0
4
0
3
Order By: Relevance
“…The average soil Ca contents were 3 mmol c dm −3 in the 0-20 cm layer (Table 1) which is considered a very low level for the development of eucalyptus [16]. On the other hand, Gazola et al [18] found that the soil K contents in the eucalyptus planting row at the superficial layer (0.00-0.20 m) at 24, 36, and 66 months after planting and from 0.20 to 0.40 m at 24 months were influenced by the dose of K 2 O (0, 90, 135, and 180 kg ha −1 ).…”
Section: Soil Chemical Analysismentioning
confidence: 93%
See 2 more Smart Citations
“…The average soil Ca contents were 3 mmol c dm −3 in the 0-20 cm layer (Table 1) which is considered a very low level for the development of eucalyptus [16]. On the other hand, Gazola et al [18] found that the soil K contents in the eucalyptus planting row at the superficial layer (0.00-0.20 m) at 24, 36, and 66 months after planting and from 0.20 to 0.40 m at 24 months were influenced by the dose of K 2 O (0, 90, 135, and 180 kg ha −1 ).…”
Section: Soil Chemical Analysismentioning
confidence: 93%
“…The initial growth attributes (DBH, height and total wood volume) did not respond to residual N doses. This can be explained partly by the presence of litter in the forest site [28] and partly by the greater mobility of N in soil, mainly in the form of nitrate in relation to P and K. Gazola et al [18] evaluated clonal eucalyptus plantation and observed that N fertilization positively influenced the growth and stem diameter of eucalyptus trees up to a maximum dose of 63 kg ha −1 at the age of eighteen months.…”
Section: Analysis Of Initial Growth (Diameter At Breast Height Height and Total Wood Volume)mentioning
confidence: 99%
See 1 more Smart Citation
“…Brazil is the world leader, producing Eucalyptus on 6 × 10 6 ha with an average yield of 36 m 3 ha −1 year −1 [ 2 ]. While Eucalyptus is adapted to low-fertility soils, nutrient supply, especially N and K [ 3 , 4 , 5 , 6 ] can limit stand productivity [ 1 , 7 , 8 ]. Fertilization was found to increase wood production of Eucalyptus grandis by 28% and irrigation by another 30% to reach potential outcome of 83 m 3 ha −1 year −1 , where the most yield-impacting factors are set at near optimum levels [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…dose 50% e tratamento com fertilizante mineral na dose recomendada para a cultura permite propor que a utilização do fertilizante organomineral não prejudica o crescimento inicial da muda (Tabela 17). Ressalta-se que o IQD constitui-se de um índice com alta variação, principalmente em razão da espécie cultivada, manejo das mudas, volume do recipiente Destaca-se que o potássio é o nutriente mais acumulado nos tecidos de plantas eucalipto, sendo o híbrido E. urophylla x E. grandis reconhecido pela sua grande eficiência na absorção e utilização desse nutriente(GAZOLA et al, 2019). DAT) to the doses 50%, 150% and 200% of the FOM.…”
unclassified